An appraisal of the credit and monetary situation in Pakistan - Meenai, Saeed Ahmedn ([Karachi] : State Bank of Pakistan, 1962)
A comprehensive appraisal of the credit and monetary situation in Pakistan in the overall framework of the Government's declared policy objectives and revised Second Five-Year Plan.
oif 29/01/2019
Loans
Keywords: Banks and banking; Credit; Bank loans